PENYEBARAN PENCEMAR UDARA DI KAWASAN INDUSTRI CILEGON(THE DISPERSION AIR POLUTANT AT CILEGON INSDUSTRY AREA) - Yayat Ruhiat; Ahmad Bey; Imam Santosa; Leopold O. Nelwan (Agromet, 2008)
The dispersion of the air polution, especially from the industry is much decided by the height of the stack, the higher the stack the farthest pollutant being emitted. To analyze the pollutant dispersion in the industrial area, Screen3 model US-EPA from Environmental Protection Agency, USA is used. This model is used to analyze the pollutant dispersion emiitted by factories. After implementing the model to various atmosphere stability, it is found that the fastest the wind velocity, the bigger the maximum pollutant concentration emitted and the smaller the distance dispersion. After implementing the model with the wind velocity of 2.45 m/s , it is found that the air pollution (SO2) in Pulomerak area, the maximum concentration of pollutan is 252.20 μg/m3 with the dispersion distance of 4664 m. Meanwhile, based on the measurement, with the same wind velocity at the same area, the maximum concentration of the pollutant is of 29.57 μg/m3. Within the atmosphere C to E, the two pollutants spread out at the range of 9921 m to 18800 m from the source.